The Formation of Chinese Ethnic Political Representation through Social Recognition in Local Public Spaces in Bangka Regency - Frans Tory Damara Pradipta; Aliyah; Sofa Sofiyanty; Riky Ovaliansyah Harahap; Aimie Sulaiman; Novendra Hidayat; Raja Hisyamudin bin Raja Sulong (Journal of Southern Sociological Studies, 2026)
Political representation of ethnic minorities is often explained through electoral competition and institutional democratization, while the role of social recognition in shaping political legitimacy remains underexplored, particularly in locally grounded democracies of the Global South. This study analyzes how social recognition contributes to the formation of Chinese ethnic political representation in Bangka Regency, Indonesia. Employing a qualitative descriptive approach, the research was conducted in Sungailiat District through in-depth interviews, observation, and documentation involving members of the Malay and Chinese communities. The data were analyzed using the interactive model of Miles and Huberman and interpreted through Honneth's Recognition Theory and Pitkin's Political Representation Theory. The findings reveal that political representation is preceded by a gradual process of social recognition manifested in social acceptance, reciprocal trust, and active participation in local public spaces. Long-standing interethnic interaction has enabled the Chinese ethnic community to gain public legitimacy, which subsequently strengthens opportunities for political representation. Rather than emerging solely from electoral processes, political representation is constructed through continuous everyday relationships embedded in neighbourhood organizations, mutual assistance, and shared civic activities. The study contributes to Southern sociological perspectives by treating Bangka not merely as a site for applying Euro-American theories, but as a location from which recognition-based political representation can be theorized. It demonstrates that, in a postcolonial multicultural setting, political legitimacy is generated through historically situated and locally meaningful practices before it is expressed through formal democratic institutions.